Irish immigrants in the land of Canaan letters and memoirs from colonial and revolutionary America, 1675 - 1815 (Oxford Univ. Press, 2003)
Publisher's description: Irish Immigrants in the Land of Canaan is a monumental study of early Irish Protestant and Catholic immigration to America. Through exhaustive research and analysis of the migrants' letters and memoirs, the editors explore why the immigrants left Ireland, how they adapted to colonial and revolutionary America, and how their experiences and attitudes shaped society, culture and politics, and created modern Irish and Irish-American identities, in America and Ireland alike.